Effect of arginine on microorganisms involved in dental caries: a systematic literature review of in vitro studies - Miranda, Marina Lins [UNESP]; Silva, Bianca Núbia Souza [UNESP]; Salomão, Karina Borges [UNESP]; de Oliveira, Analú Barros [UNESP]; Gabbai-Armelin, Paulo Roberto [UNESP]; Brighenti, Fernanda Lourenção [UNESP] (My University, 2020)
This systematic review aimed to discuss the effects of arginine on caries-related microorganisms in different in vitro biofilm models. The eligibility criteria were in vitro studies that evaluated the effect of arginine at different concentrations on caries-related microorganisms using biofilm models. Eighteen studies published between 2012 and 2019 were included. Different bacterial species were studied. Seventeen studies (94.4%) achieved a low risk of bias and only one showed a medium risk of bias. The studies showed that arginine is a promising approach for the ecological management of dental caries. The focus of this review was to evaluate the effects of arginine on microorganisms involved in the mechanism of dental caries.
Keywords: Arginine; dental caries; microorganisms in vitro studies